English Terms in Live Shopping E-Commerce as Authentic Materials for Teaching ELF Learners for ESP Vocabulary and Speaking Skills - Tira Nur Fitria (Jurnal Bahasa Asing, 2026)
This research analyzes and identifies English terms commonly used in live shopping e-commerce platforms and investigates their potential as authentic materials for developing EFL learners’ vocabulary and speaking skills. This study employs a descriptive qualitative research design. The study identified and categorized English terms commonly used in live shopping e-commerce platforms, specifically Shopee and TikTok, based on their function in live interactions. Terms were grouped into Promotions & Discounts, Urgency & Time, Products & Quality, Transactions & Payments, Digital Engagement & Interaction, Fun/Trendy/Review, and Other/General Marketing Terms. These expressions are strategically employed by hosts to attract viewers, encourage purchases, and maintain engagement in real time. The findings show that these terms appear in both spoken and written communication, including product descriptions, live announcements, and chat interactions. They provide authentic materials for EFL learners, offering practical language for developing vocabulary and speaking skills across persuasive, transactional, interactive, descriptive, and professional communication contexts in digital commerce. The study also found that live hosts on Shopee and TikTok frequently use English terms in both spoken and written communication during live shopping sessions. These terms, drawn from promotions, product descriptions, transactions, digital engagement, and marketing interactions, serve strategic purposes such as attracting viewers, encouraging purchases, and maintaining engagement. They were categorized into seven functional groups: Promotions & Discounts, Urgency & Time, Products & Quality, Transactions & Payments, Digital Engagement & Interaction, Fun/Trendy/Review, and Other/General Marketing Terms. These English terms provide authentic material for EFL learners, offering exposure to real-world, contextually meaningful language. They support vocabulary expansion, transactional speaking, persuasive and promotional skills, interactive communication, descriptive and evaluative speaking, as well as marketing and strategic discourse. By integrating these terms into classroom activities such as role-plays, simulations, and presentations, learners can develop functional and professional English skills applicable to digital commerce contexts.